Ordinary muon capture and $$γ $$ γ competition in76As supporting calculations for $$0ν β β $$ 0 ν β β decay - Peter Grabmayr (European Physical Journal C: Particles and Fields)
Abstract The compound nucleus model is employed to calculate partial $$γ $$ γ -decay width $$Γ _γ $$ Γ γ of states in 76As highly excited above the neutron binding energy. The calculations demonstrate the need to observe the $$γ $$ γ competition above neutron threshold when extracting the population of low-lying excited states in 76As after muon capture on 76Se. Decay and feeding schemata can be modeled to support the extraction of partial muon capture rates. The latter are needed when results of ( $$μ ^-,ν $$ μ - , ν ) reactions are used in tests of model calculations for nuclear matrix elements of neutrinoless double beta decay.